WHEN ALGORITHMS MEET ANATOMY: UZBEKISTAN'S MEDICAL EDUCATION IN THE AGE OF TECHNOLOGY - Bazarbaev M.I., Sayfullaeva D.I. , (Central Asian Journal of Medicine, 2025)
In the context of rapid digital transformation, medical education in the Republic of Uzbekistan is experiencing significant qualitative shifts.This article examines the growing role of information technologies — including artificial intelligence — in shaping the professional training of future healthcare providers. Particular attention is paid to interdisciplinary approaches, the enhancement of analytical and diagnostic skills, and the integration of digital responsibility and medical ethics into the learning process. Using the example of the Tashkent Medical Academy, the article highlights how modern platforms and simulation technologies facilitate the development of competent, practice-ready specialists. The study aims to underscore the pedagogical significance of digital innovations in fostering both professional competence and a deep sense of humanism and ethical responsibility among medical students.